Reducing COD Levels of Batik Waste Using Chicken Egg Shells and Tea Dregs - Puspita, Anggrek Sinar; Fatmawati, Zulaikhah; Paramita, Vita (Vocational College of Universitas Diponegoro, 2022)
In the last ten years, the batik industry has experienced very rapid growth. This provides benefits but also has adverse effects on humans and the environment because the sector generates waste. Batik liquid waste contains chemical compounds that can increase the COD value. Alternative treatment of liquid waste from batik factories is the biosorption process using biosorbent from chicken egg shells and tea dregs. This study aimed to investigate the effect of variations in the biosorbent ratio, contact time, and initial pH of the sample on changes in COD. In this study, the acid activation method was used to increase the ability of the biosorbent to absorb the COD content in the batik industry wastewater. This research method uses the Response Surface Methodology (RSM) method, where the biosorbent made is then contacted with batik wastewater to determine the decrease in COD levels contained in it. The critical value was achieved when the material ratio was 12.3270 grams of eggshell, with a contact time of 47.1281 at a pH of 1.71281. The best results were obtained in sample 5 with a biosorbent ratio of 11.25:3.75, contact time of 50 minutes, and initial pH 2 with a decrease in COD levels of 77%.